Effect of egg size, age of hen and storage period on fertility, hatchability, embryo mortality and chick malformations in eggs of japanese quail (Coturnix coturnix japonica) - Rabiatul Adawiah Othman; Md. Ruhul Amin; Shafiqur Rahman (2014)
This study was conducted to investigate the effect of egg size, age of hen and storage period of eggs before incubation on fertility, hatchability, embryo mortality and chick malformations in Japanese quail (Coturnix coturnix japonica). The study was carried out in quail farm located at Tanah Merah, Kelantan. Totally 1441 eggs of quail were set into the incubator by applying 9 treatments groups: 3 groups for egg size (6-7 g, 8-9 g and 10-ll g), 3 groups for hen age (≥3 - <5 month,≥5 - <8 month and ≥8 - <10 month) and 3 groups for egg storage period (≥4 - ≤6 days, ≥7 - ≤9 days and ≥10 - ≤14 days). Records on fertility, hatchability, embryo mortality and chick malformations were taken from each hatch. Analysis of variance (ANOVA) revealed that the egg size had highly signiﬁcant (P< 0.01) effect on hatchability and embryo mortality in quails and was not found to be signiﬁcant (P>0.05) on fertility and chick malformations. The age of hen had insigniﬁcant (P>0.05) effect on every aspect except fertility. Storage period had highly signiﬁcant (P<0.0l) effect on fertility, hatchability and embryo mortality rate. Results from this study concluded that heavy egg weight (10-ll g), middle aged hen (≥5 - <8 month) and shortest storage period (≥4 - <6 days) gave the best hatching performances.